Enkephalin knockout male mice are resistant to chronic mild stress. (26th May 2014) - Melo, I.; Drews, E.; Zimmer, A.; Bilkei‐Gorzo, A.
Abstract : Enhanced stress reactivity or sensitivity to chronic stress increases the susceptibility to mood pathologies such as major depression. The opioid peptide enkephalin is an important modulator of the stress response. Previous studies using preproenkephalin knockout (PENK KO) mice showed that these animals exhibit abnormal stress reactivity and show increased anxiety behavior in acute stress situations. However, the consequence of enkephalin deficiency in the reactivity to chronic stress conditions is not known. In this study, we therefore submitted wild‐type (WT) and PENK KO male mice to chronic stress conditions, using the chronic mild stress (CMS) protocol. Subsequently, we studied the CMS effects on the behavioral and hormonal level and also performed gene expression analyses. In WT animals, CMS increased the expression of the enkephalin gene in the paraventricular nucleus (PVN) of the hypothalamus and elevated the corticosterone levels. In addition, WT mice exhibited enhanced anxiety in the zero‐maze test and depression‐related behaviors in the sucrose preference and forced swim tests. Surprisingly, in PENK KO mice, we did not detect anxiety and depression‐related behavioral changes after the CMS procedure, and even measured a decreased hormonal stress response. These results indicate that PENK KO mice are resistant to the CMS effects, suggesting that enkephalin enhances the reactivity to chronic stress. Abstract : PENK KO mice are resilent to chronic mild stress: CMS elicited anhedonia and despair‐like behaviour in wild‐type but not in PENK KO mice.